New hybrids that out-yielded the released hybrid AR051H by 20-47% identified for Senegal and Cote d'Ivoire - CGIAR Research Program on Rice (2020)
22 new hybrids that out-yielded the hybrid released in Senegal ISRIZ-09 (AR051H) by 20-47% were identified in the 2020 dry season and were further tested in 3-replicated trial in the wet season of 2020 at Mbe, Cote d'Ivoire.